Implementation of Prognostic Cloud Ice Number Concentrations for the Weather Research and Forecasting (WRF) Double‐Moment 6‐Class (WDM6) Microphysics Scheme - Sun‐Young Park; Kyo‐Sun Sunny Lim (Journal of Advances in Modeling Earth Systems, 2023)
Abstract The ice microphysical processes in the Weather Research and Forecasting (WRF) Double‐Moment 6‐class (WDM6) microphysics scheme are treated as a single‐moment approach, in which the number concentration of cloud ice is diagnosed based on its mixing ratio. This study develops the revised WDM6 scheme through the implementation of prognostic cloud ice number concentrations. The effect of the prognostic number concentration on the simulated precipitation is verified through simulations of short‐term winter snowfall cases during International Collaborative Experiments for the Pyeongchang 2018 Olympics and Paralympics (ICE‐POP 2018) winter games and a 1‐month regional climate case during the summer season, July 2009. For all cases, the revised WDM6 simulates higher cloud ice number concentrations and lower cloud ice mixing ratios than the original WDM6. The microphysics budget analysis for the snowfall cases shows that the inefficient deposition and vapor freezing nucleation processes of cloud ice reduce the available cloud ice mixing ratio. Consequently, the accretion processes with cloud ice decrease and the deposition into snow increases due to the surplus water vapor. The revised WDM6 alleviates the positive bias of surface precipitation consisting of snow over the region where the original WDM6 simulates excessive precipitation, compared to the observed data. For the regional climate case, the reduced cloud ice amount strengthens the Western North Pacific high‐pressure system by allowing more solar radiation to reach the surface, leading to simulated precipitation bands and synoptic environments that are more comparable with the observed data.